PEMBUATAN APLIKASI PENYIMPANAN OBAT BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT: PEMBUATAN APLIKASI PENYIMPANAN OBAT BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Maria, Elsa; Selviana, Renita; Khadavi Setiyansyah, Muhammad (Jurnal Sistem Informasi Aplikasi Teknologi Informasi, 2024)
Abstract : The Polindes of Sidowayah Village is a form of community participation in providing birthing aids and community health services, including family planning, maternal and child health, and other health services. At present the Polindes of Sidowayah Village has several obstacles, such as recording drug data which is still written down manually so that manual recording and checking of drugs is inefficient, there are frequent delays in preparing drug inventory reports, and there is a lot of accumulation of expired drugs stored due to very long drug monitoring and have not implemented the FEFO system. To overcome this problem, a web-based drug supply information system was developed